PENERAPANMODEL PEMBELAJARAN ELICITING ACTIVITIES (MEAs) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS X SMAN 1 SEKOTONG PADA MATERI POKOK PERBANDINGAN TRIGONOMETRI - Ulfah, Maria; Abidin, Zainal (Media Pendidikan Matematika, 2016)
The problem in mathematics learning in SMA Negeri 1 Sekotong is the low student activity and student learning outcomes. This study aims to improve the student activity and learning outcomesat X Grade student of SMA Negeri 1 Sekotong through the application of Eliciting Activities (MEAs) learning models. This research is classroom action research (PTK). The sample in this study Grade X of SMA Negeri 1 Sekotong in the school year 2015/2016 as many as 31 students. The instrument used to measure students activity is observation sheet and student learning outcomes abstained from the test evaluation of student learning. Based on the analysis of data abstained activity score of student learning cycle I and II was 2.96 and 3.85 with active category to the category of very active. Scores of individuals obtained depending on how many current behavior of a number of indicators were observed. While analysis learning outcomes of student in the first cycle showed that of the 31 students who took the tests, as many as 24 students completed with an average grade completeness reached 77.41% and analysis learning outcomes of student in the second cycle showed that of the 31 students who took the tests, as many as 30 students completed with an average grade completeness reached 96.77%. The completeness criteria individually seen when students getÂ  â‰¥ 75 as thestandard mastery learning minimal and classical completeness by using the value of the theory of mastery learning outcomes minimalstating that the class is said to be completed by learning when reached at least 85% of the number of students who received grades of 75 and above. Thus we can conclude thatThe Application Of Eliciting Activities (Meas) LearningModel To Increase Student Activity and Learning Out Comes At X Grade Students Of SMAN 1 Sekotong On Subject Matter Comparison Of TrigonometryIn Academic Year 2015/2016effectively